The emergence and impact of market institutions: The wolesale market for fish and other perishable commodities - Sandro Sapio; Alan Kirman; Giovanni Dosi (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2011)
This work introduces a special issue of the Journal of Economic Behavior and Organization on the emergence and impact of market institutions in wholesale fish markets. The analysis of fish markets has a respectable pedigree also in terms of the description of how they function. A major advantage of the analysis of fish markets in this literature is that it often gathers and exploits information that is typically hot available in official market statistics. A full understanding of market dynamics, for example, is easier to obtain ifone can observe not only the final outcomes of bilateral transactions which are not observed by other market participants, but also thesocalled transactions that did not happen, i.e. offers and counteroffers that were refusedby the trading parties. Fish markets exhibit two feature that make their analysis appealing for economists. On the one hand, fish is a perishable good, and because stocks cannot be carried over from one day to he next, the formal analysis of this market is simpler. Indeed, with noinventories, successive market sessions can be thought of as independent, at least approximately. the second intriguing feature is that the organiation of fish markets varies from location to location wit little obvious reason, some with pairwise trading, where prices ar not posted, and others based on auctions, where, by definition, price information is centralized and publicly available. Such observed differences help also in in understanding ho individual learning and adaptation take place under different market architectures, how markets adjust to disequilibria, and to what extent collective rationality is rooted in individual rationality. The research questions covered by the selected papers include, first, the impact of decentralized pairwise bargaining versus centralized auctions on the statistical properties of fish prices and trades volumes; and second, the ways information-processing, decision-making capabilities and behavioral rules are deployed by agents and influenced by market set-ups and market size.
Keywords: F2; M14; K0; C23; 330; fish markets; market institutions; aggregation; learning